Evaluation of end-user satisfaction among employees participating in a web-based needs assessment inventory - Wan Norizan, Wan Hashim; Mohd Razali, Otman; Safi’ee, Madian; Mohamad Izzat, Syafiq (Elsevier Ltd., 2013)
This paper reports on the end-user satisfaction evaluation of ENAI. It highlights the positive impact and effect of online web- based management system for counseling inventory. Participants have reported satisfaction with ENAI and the service impact within community of users is complementary. Improvement of ENAI can be made to enhance the end-user satisfaction by referring to the user's requirements.